PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI RESTORAN LAMODA JAKARTA - Febri Aria Saputra; Agus Riyanto (LPPM Universitas Asa Indonesia, 2015)
Purpose- is to findout the effect of compensation and motivation against employee’s performance in Lamoda Restaurant, Jakarta. Design/methodology/approach- The respondents were all staffs of Lamoda. Data collected using quesionaire, and analyzed by multiple regression. Findings-It is concluded that compensation is a basic element of motivation to increase the performance of employees in Lamoda restaurant. Research limitations- The limited sample and variable assigned in this research that can be extended in the future research Practical implications- The scheme of compensation in Lamoda to be concentrated by its management as the key to motivate them for the maximum achievement The Originality- Usage of primary data as the basis of this research